A Primary Squamous Cell Carcinoma of the Thyroid Presenting as the Anaplastic Thyroid Carcinoma: A Case Report - Zheng, Rui-zhe; Huang, Guo-hui; Xu, Ying-jie (Frontiers in Surgery, 2020)
Background: Primary squamous cell carcinoma of the thyroid (PSCCT) is an uncommon malignancy that is difficult to diagnose and differentiate. There is no consensus for the early clinical, radiological or ultrasonic identification of PSCCT before pathological changes are observed in patients. There is also no suitable treatment due to the absence of a definite diagnosis. Case presentation: A 76-year-old female patient complained about a rapidly growing cervical mass, dyspnea, dysphagia, and a change in her voice. Based on the results of thyroid ultrasound, fine needle aspiration, and plain and enhanced CT, the patient was initially diagnosed with Anaplastic Thyroid Carcinoma (ATC). Thereafter, we removed the mass that was the patient’s main complaint. The gross examination of the patient’s symptoms also supported our previous diagnosis. However, her disease was finally diagnosed as PSCCT, according to the histopathology and immunohistochemistry findings of the mass. Conclusion: Our case highlights the need for a comprehensive framework in the management of PSCCT. The more auxiliary examinations (e.g. ultrasonographic, radiology or biopsy examinations) that we take, the more likely we are to identify this disease. Immunohistochemistry is currently the preferred examination for the diagnosis of PSCCT while surgical resection combined with radio-sensitizing therapy and adjuvant chemotherapy is the main treatment methods for PSCCT.